Reaction of winter wheat and barley cultivars to Fusarium pseudograminearum‐inoculated fields in the dryland Pacific Northwest, USA. Issue 2 (29th May 2021) - Hagerty, Christina H.; Lutcher, Larry; McLaughlin, Katherine; Hayes, Patrick; Garland‐Campbell, Kim; Paulitz, Timothy; Graebner, Ryan C.; Kroese, Duncan
Abstract: Fusarium crown rot (FCR) of winter wheat ( Triticum aestivum L.), caused by Fusarium pseudograminearm and Fusarium culmorum, is a yield‐limiting disease in arid wheat‐producing areas of the inland Pacific Northwest. Foliar fungicide applications and currently available seed treatments do not control FCR. Alternative crops that provide a rotational benefit to reduce disease are not economically feasible. Major‐gene resistance is unavailable, but there is preliminary evidence that some wheat and barley ( Hordeum vulgare L.) cultivars are more resistant than others. We followed up on preliminary work by growing 14 varieties of winter wheat, planted with in‐furrow FCR inoculum, in 2018 and 2019 in Morrow County, Oregon—one of the world's driest wheat producing regions. Two barley cultivars were added to the experiment during the second year of research. Evaluations of cultivar resistance were made by conducting aboveground visual assessments by counting whiteheads, prematurely senesced wheat heads that are indicative of FCR infection. Whitehead count information was correlated with yield and grain volume weight data. Maximum whitehead counts were measured in plots of the FCR‐susceptible check cultivar 'Stephens'. There was no evidence of a cultivar‐specific relationship between whitehead count and corresponding values for yield and grain volume weight. There was limited evidence that some cultivars have the capacity to compensate for effects of disease. Core Ideas: There is evidence that some wheat cultivars have the capacity to compensate for Fusarium crown rot (FCR). It is necessary to corroborate whitehead counts with FCR symptomology on crown tissue. The contradiction of whitehead count data and yield may be due to increased tillering capacity.